Um estudo sobre amplificadores de RF faixa larga - Adami, Ant?nio Rodolpho Carneiro (2006)
ABSTRACT: The design of wide band RF amplifiers for CATV networks and wide band data networks, which achieve the specifications needed to handle hundreds of analogic and digital channels, must to be carry out, not only with computers but also with detailed modeling of all components. First, we started choosing a configuration that could provide the best distortion reduction: the cascode configuration. Then, a set of design equations, which related the first order circuit behavior to its main components were developed. We observed good accuracy of these equations in frequencies as high as 300 MHz, neglecting the effect of the parasite elements. Then, we modeled a enhanced circuit, taking into account the main parasite elements. So, the nodal method was applied with the purpose to obtain the nodal conductance matrix, which represents the circuit with N nodes. Applying the Gauss-Jordan method to these equations system, the number of access points were reduced to only 2. At this point we obtained a y matrix corresponding to the input and output ports. Then, it was possible to obtain the mains circuits parameters such as the transductor gain, the input return loss and the output return loss. Finally, after the linear analysis, a nonlinear analysis was performed in laboratory. The results of the measurements in the prototypes validated our approach.